2019
DOI: 10.1016/j.ihj.2019.11.256
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome in patients with a delayed presentation after ST-elevation myocardial infarction and complicated by cardiogenic shock

Abstract: Objective Delayed presentation after ST-elevation myocardial infarction (STEMI) and complicated by cardiogenic shock (CS-STEMI) is commonly encountered in developing countries and is a challenging scenario because of a delay in revascularization resulting in infarction of a large amount of the myocardium. We aimed to assess the clinical characteristics, angiographic profile, and predictors of outcome in patients with a delayed presentation after CS-STEMI. Methods A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…The mortality in patients with cardiogenic shock was 37.3% which is comparable to a similar study done in our institute which showed a mortality of 42.9%. 18 Female gender was associated with increased mortality rates (OR-3.306) which was higher than from other Indian registries like DEMAT 15 (OR-1.4), HP-ACS 8 (OR 1.36 C.I. 0.77–2.38) and Kerala -ACS 7 (OR−1.05, C.I.−0.8–1.38) registries.…”
Section: Discussionmentioning
confidence: 77%
“…The mortality in patients with cardiogenic shock was 37.3% which is comparable to a similar study done in our institute which showed a mortality of 42.9%. 18 Female gender was associated with increased mortality rates (OR-3.306) which was higher than from other Indian registries like DEMAT 15 (OR-1.4), HP-ACS 8 (OR 1.36 C.I. 0.77–2.38) and Kerala -ACS 7 (OR−1.05, C.I.−0.8–1.38) registries.…”
Section: Discussionmentioning
confidence: 77%
“…Heart failure was the most common complication. ** * * Fair Sharma et al, 2019 [29] Prospective, cross-sectional, observational. 1 tertiary care hospital in India.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were treated with dual antiplatelets, statin, and low-molecular-weight heparin. As reported previously, 10 due to the significantly late presentation to our center, the decision of revascularization was based on delay from symptom onset, presence of anginal pain/electrical instability, hemodynamic parameters, end-organ failure, myocardial viability, mechanical complications, coronary anatomy, and patient consent and willingness for revascularization. The primary end-point of the study was in-hospital mortality.…”
Section: Methodsmentioning
confidence: 99%